Peningkatan Keterampilan Literasi Membaca Permulaan Melalui Media Flash Card Pada Siswa Kelas 1 A UPT SPF Inpres Bira 2 - Nurhaedah (Universitas Negeri Makassar, 2023)
The problem that is the background of this research is the low literacy skills of the beginning reading students in grade 1 A UPT SPF Inpres Bira 2. This study aims to describe the use of Flash Card media to improve literacy skills at the beginning of grade 1 A students at UPT SPF Inpres Bira 2. The research used was a type of classroom action research (PTK) which consisted of 2 cycles, each cycle consisting of 4 meetings with stages of activities in the form of planning, implementing, observing, and reflecting. The focus of this research is the use of Flash Card media to improve students' early reading literacy skills. The research subjects were class 1 A students at UPT SPF Inpres Bira 2 in the even semester of the 2023/2024 school year, which consisted of 16 students. Data collection techniques in this study used tests, observation, and documentation. Qualitatively the collection instrument used an observation sheet and quantitatively used a preliminary reading skills test. The data analysis technique used is descriptive quantitative and qualitative data analysis. The results showed that there was an increase in initial reading literacy skills in the learning process, as evidenced by the class average score of the pre-action was in the sufficient category (C), in cycle I it increased but was still in the sufficient category (C) while in cycle II experienced an increase and is in the good category (B). The increase is based on the initial reading literacy skill process using Flash Card media so that the initial reading literacy skills of class 1 A UPT SPF Inpres Bira 2 can experience an increase.